2018
DOI: 10.1152/ajpgi.00390.2017
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein stenosis preconditioning of living donor liver in swine: early mechanisms of liver regeneration and gain of hepatic functional mass

Abstract: To reduce the morbidity and mortality risk for the donor in living donor liver transplantation (LDLT), we previously identified 20% left portal vein (LPV) stenosis as an effective preconditioning method to induce cell proliferation in the contralateral lobe without downstream ipsilateral atrophy. In this study, we report the pathways involved in the first hours after preconditioning and investigate the changes in liver volume and function. Fourteen pigs were used this study. Five pigs were used to study the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Chen et al [43] performed a bio-artificial liver treatment using 200 g of spheroid reservoir bio-artificial liver (SRBAL) to promote liver regeneration after 85% hepatectomy, observing an increment in IL6 and TGFβ values, but not in TNFα. Instead, Brige et al [45] demonstrated that portal vein stenosis preconditioning could determine higher values of IL6, IL10, HGF, and TNFα, even without liver resection.…”
Section: Liver Regeneration Monitoringmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al [43] performed a bio-artificial liver treatment using 200 g of spheroid reservoir bio-artificial liver (SRBAL) to promote liver regeneration after 85% hepatectomy, observing an increment in IL6 and TGFβ values, but not in TNFα. Instead, Brige et al [45] demonstrated that portal vein stenosis preconditioning could determine higher values of IL6, IL10, HGF, and TNFα, even without liver resection.…”
Section: Liver Regeneration Monitoringmentioning
confidence: 99%
“…Nine articles evaluated liver regeneration as a response to PVE, PVL, and ALPPS. In particular, Asencio et al described how a PVE performed 24 h before a 90% hepatectomy could affect the regenerative process [49], while Brige et al used PVE to generate a 100% stenosis to be compared to a partial 20% stenosis of the portal vein [45]. Gaillard et al proposed a new technique, making a comparison between standard permanent PVE and reversible PVE through an absorbable material, finding that repeated reversible PVE (with a second PVE treatment 14 days after the previous one) could boost liver hypertrophy more than the other "one-shot" treatments [29].…”
Section: Direct Hepatectomy and Staged Hepatectomymentioning
confidence: 99%
See 2 more Smart Citations
“…Existen modelos experimentales de PVL también en animales grandes como el llevado a cabo en 2018, en un modelo porcino. Este modelo objetivó, a través de análisis genéticos, moleculares y celulares, que la estenosis del 20 % de la vena porta izquierda desencadenaba la fase de preparación de la regeneración hepática en el lóbulo contralateral e involucraba a TNF-α, IL-6 y óxido nítrico sintasa 2, responsables de un aumento en la capacidad funcional y en el volumen hepático total [98]. En otro modelo porcino publicado en el mismo año, se observó que la administración de citoquinas (IL-6 y TNF-α), un anticuerpo monoclonal contra TGF-β1 (MAB TGF-β1) y células madre mesenquimales en las ramas portales no ocluidas inmediatamente tras PVL, inducía un crecimiento más rápido del volumen del FLR [99].…”
Section: Detallamos Este Modelo Más Adelanteunclassified